Back Cover: Synthesis and Biological Evaluation of Imidazopyridine–Oxindole Conjugates as Microtubule‐Targeting Agents (ChemMedChem 12/2013). Issue 12 (December 2013) - Kamal, Ahmed; Reddy, Vangala Santhosh; Karnewar, Santosh; Chourasiya, Sumit S.; Shaik, Anver Basha; Kumar, G. Bharath; Kishor, Chandan; Reddy, M. Kashi; Narasimha Rao, M. P.; Nagabhushana, Ananthamurthy; Ramakrishna, Kallaganti V. S.; Addlagatta, Anthony; et al.
<x xml:space="preserve">Abstract</x> The back cover picture shows the predicted interaction of an imidazopyridine–oxindole conjugate with β‐chain amino acids of tubulin. A series of conjugates were designed, synthesized and evaluated as microtubule‐targeting agents. Molecular modeling predicts that these conjugates bind in the colchicine binding site at the interface between the α‐ and β‐chains of tubulin. For more details, see the Full Paper by Ahmed Kamal, Anthony Addlagatta, Srigiridhar Kotamraju, et al. on p. 2015 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>